Cervical Facet Arthrography. Issue 1 (January 1985) - Wedel, Denise J.; Wilson, Peter R.
Abstract : Cervical arthrography was performed on 13 patients with putative cervical facet symptoms. Under fluoroscopic control, injection of radiopaque dye, local anesthetic, and depot steroid into the affected joint capsule was performed without complication. Eleven of the 13 patients had partial to complete pain relief during the 2-week to 6-month followup period.